Screening of Genes Related to Resistance to Bacterial Leaf Blight in Oryza officinalis by using RNA-seq Technology - Yayun YANG; Feifei ZHANG; Famei ZHANG; Xinxiang A; Chao DONG; Cuifeng TANG; Chunyun YANG; Luyuan DAI (Guangdong nongye kexue)
【Objective】Oryza officinalis belongs to the CC chromosome group of rice genus, and it had accumulated a large number of resistance genes that adapt to harsh environments during long-term natural survival. Based on transcriptome sequencing (RNA-seq), disease resistance related genes could be discovered, laying a foundation for researches on gene function and regulatory mechanisms.【Methods】Two isolates of Xanthomonas oryzae pv. oryzae CX28-3 and PXO99 were inoculated to 38 O. officinalis wild rice materials of 6 populations (Ⅰ-Ⅵ) from Yunnan Province, and different resistance phenotypes were evaluated. The highly resistant and susceptible populations were selected for transcriptome sequencing. The transcriptome sequencing data of O. officinalis 36 (resistant) and O. officinalis 37 (susceptible) plants after PXO99 inoculation stress at 0, 24, and 48 h were analyzed. And genes related to resistance to bacterial leaf blight in O. officinalis wild rice were predicted.【Results】The 38 O. officinalis wild rice materials from 6 populations showed different disease resistance to 2 strains (CX28-3 and PXO99), and the overall resistance rate was medium or above, among which the highest resistance rate was 93.50% in Ⅴ population and the lowest rate was 62.50% in Ⅲ population. Among them, it was found that 5 accessions of O.officinalis were susceptible to CX28-3 isolate, with a disease infection rate of 13.15%, and 42.10% to PXO99 strain, indicating that PXO99 had strong pathogenicity. There were 20 O. officinalis materials resistant to two strains simultaneously, accounting for 66.67% of all materials. O. officinalis 37 showed moderate susceptibility to both strains, while O. officinalis 36 showed resistance to both strains. Through transcriptome sequencing of O. officinalis 36 and 37 plants, a total of 75 650 differentially expressed genes (DEGs) were identified. GO functional enrichment analysis revealed that PXO99 treatment resulted in a total of 45 significantly enriched GO categories in biological processes. Among them, the most enriched DEGs were concentrated in cellular processes, metabolic processes, cellular anatomical entities, binding, catalytic activity, etc. KEGG enrichment analysis showed that 19 KEGG pathways were significantly enriched in the resistant and susceptible O. officinalis materials, among which KEGG pathways related to disease resistance to proteins were significantly enriched and increased. This further clarified that the resistance to disease of the O. officinalis 36 was significantly stimulated by the Xanthomonas oryzae pv. oryzae. A total of 256 common DEGs were screened, and 11 genes were closely related to the resistance to bacterial leaf blight in O. officinalis; Unigene1184, Unigene15669, CL1239, CL1421, CL4899, CL660, and CL7463 genes were up-regulated in resistant materials and down-regulated in susceptible materials. Unigene18206, CL210, CL3554, and CL9248 genes were down-regulated in resistant materials and up-regulated in susceptible materials.【Conclusion】38 accessions of O. officinalis of 6 populations from Yunnan showed different disease resistances to two strains (CX-28 and PXO99), but overall resistance was moderate or above. By using transcriptome sequencing technology, 11 genes related to resistance to bacterial leaf blight in O. officinalis were obtained. The research results will provide references for the exploration and functional study of genes related to resistance to bacterial leaf blight in O. officinalis.